Hubungan Tingkat Kepatuhan Minum Obat Terhadap Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe-2 di Instalasi Farmasi Rawat Jalan Rumah Sakit Dr. Hafiz Cianjur: The Relationship Between Medication Compliance and Blood Sugar Levels in Type-2 Diabetes Mellitus Patients at the Outpatient Pharmacy Installation of Dr. Hafiz Hospital, Cianjur - Siti Robiah; Lulu’ul Badriyah; Atika Jaya Rani (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2024)
Diabetes Mellitus Type 2 is at risk of having cardiovascular disease, such as heart disease, stroke, and high blood pressure. Compliance has a significant effect on the quality of life of people with diabetes mellitus. This study was conducted with the aim of knowing the relationship between medication consumption adherence and blood sugar levels in type 2 diabetes mellitus patients at Dr. Hafiz in 2023. This research was conducted using a non-experimental research design with cross-sectional research. The total population visiting Dr. Hafiz Cianjur Hospital from January 2023 was 160 patients. By collecting quantitative data through questionnaires for patients selected by a purposive sampling method, 114 samples were obtained. The analysis used in this study uses univariate and bivariate analysis. The results of the study found that as many as 64.9% of respondents had a low level of compliance, with the majority of respondents having high blood sugar levels (69.3%). The results of statistical analysis showed a p-value of 0.000 ≤ 0.05; there was a significant relationship between medication adherence and blood sugar levels in type 2 diabetes mellitus patients at Dr. Hafiz Cianjur Hospital.